Usefulness of normal saline for sealing the needle track after CT-guided lung biopsy. Issue 11 (November 2015) - Li, Y.; Du, Y.; Luo, T.Y.; Yang, H.F.; Yu, J.H.; Xu, X.X.; Zheng, H.J.; Li, B.
<x xml:space="preserve">Abstract</x> Aim To determine whether the use of normal saline for sealing the needle track can reduce the incidence of pneumothorax and chest tube placement after computed tomography (CT)-guided lung biopsy. Materials and methods A prospective, randomised, controlled trial enrolling 322 patients was conducted. All patients were randomly assigned to one of two groups: those in whom the needle track was not sealed with normal saline (n=161, Group A) and those who did receive normal saline (n=161, Group B). CT-guided biopsy was performed with coaxial technique. Normal saline, which ranged from 1–3 ml, was injected while the trocar needle was being withdrawn. Patient characteristics, lesion, and procedure variables were analysed as potential risk variables for occurrence of pneumothorax and chest tube placement. Results The incidence of pneumothorax was 26.1% in Group A and 6.2% in Group B (p<0.001). Nine patients in Group A and one patient in Group B required chest tube placement (p=0.010). Using multiple logistic regression analysis, smaller lesion size, greater needle–pleural angle, longer lesion–pleural distance, presence of emphysema, and no sealing the needle track with normal saline were significantly associated with an increased risk of pneumothorax, and that the latter three factors were also associated with an increased risk of pneumothorax requiring chest tube placement. Conlusion Normal saline for sealing the needle track significantly reduces the incidence of pneumothorax and prevents subsequent chest tube placement after CT-guided lung biopsy.